Pharmacological Chaperones: A Therapeutic Approach for Diseases Caused by Destabilizing Missense Mutations - Liguori, Ludovica (Int J Mol Sci, 2020)
The term “pharmacological chaperone” was introduced 20 years ago. Since then the approach with this type of drug has been proposed for several diseases, lysosomal storage disorders representing the most popular targets. The hallmark of a pharmacological chaperone is its ability to bind a protein specifically and stabilize it. This property can be beneficial for curing diseases that are associated with protein mutants that are intrinsically active but unstable. The total activity of the affected proteins in the cell is lower than normal because they are cleared by the quality control system. Although most pharmacological chaperones are reversible competitive inhibitors or antagonists of their target proteins, the inhibitory activity is neither required nor desirable. This issue is well documented by specific examples among which those concerning Fabry disease. Direct specific binding is not the only mechanism by which small molecules can rescue mutant proteins in the cell. These drugs and the properly defined pharmacological chaperones can work together with different and possibly synergistic modes of action to revert a disease phenotype caused by an unstable protein.